Abnormal fasting, post-load or combined glucose values on oral glucose tolerance test and pregnancy outcomes in women with gestational diabetes mellitus. (March 2020) - Papachatzopoulou, Eftychia; Chatzakis, Christos; Lambrinoudaki, Irene; Panoulis, Konstantinos; Dinas, Konstantinos; Vlahos, Nikolaos; Sotiriadis, Alexandros; Eleftheriades, Makarios
Abstract: Aims: This study aimed to investigate whether pregnancies complicated by gestational diabetes mellitus (GDM) present differences in the outcomes according to the findings on oral glucose tolerance test (OGTT), including fasting, post-load or combined abnormal blood glucose. Materials: This was a prospective cohort study including 831 singleton pregnancies with GDM per the IADPSG criteria. According to their fasting blood glucose value on OGTT the women were categorized in three groups: (i) GDM women with fasting plasma glucose levels > 92 mg/dl and normal post-load values (T0 abnormal group), (ii) patients with abnormal values at 60′ and/or 120′ and normal fasting values (T-post group) and (iii) patients with combined fasting and post-load abnormal blood glucose values (T-comb). Regression analysis was used to test the independent contribution of the different groups, along with maternal and fetal characteristics, in prediction of (i) large for gestational age (LGA), (ii) need for insulin treatment and (iii) birthweight centile. Results: GDM with abnormal fasting blood glucose was an independent risk factor for LGA (OR 2.91, 95% CI 1.33–6.36) and was associated with higher birthweight centile (10.25, 95% CI 0.27–20.25). GDM with combined fasting and post-load abnormal blood glucose was an independent risk factor for insulin treatment (OR 2.94, 95% CI 1.93–4.47). Conclusions: Women with GDM and abnormal fasting blood glucose are at increased risk for large for gestational age neonates, while women with GDM and combined fasting and post-load abnormal blood glucose are at increased risk for insulin therapy.